1981
DOI: 10.1002/cber.19811141006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclit‐Reaktionen, IV 1) Synthese von enantiomerenreinen Conduriten und Amino‐Conduriten

Abstract: Die S:hlusselzwischenstufe fur alle hier beschriebenen Synthesen ist das 1-0-Tosylat 7 des Quebrachits (l), aus dem uber 8 die 1 L-Form des Condurits B ( 5 ) und uber 13 die 1 L-Form des Condurits F (17) Cyclitol Reactions, IV *) Synthesis of Enantiomeric Conduritols and Amino-ConduritolsThe key-intermediate for all syntheses described in this paper is the 1-0-tosylate 7 of quebrachitol (1). This leads, via 8, to the 11-conduritol B (5) and, oia 13, to the 1 L-conduritol F (17). Selective displacement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In 1958, Angyul et al [14] presented a synthesis of (+)-condurito1 E ( = 1~-cyc~ohex-5-ene-l,2/3,4-tetro~; (+)-5). In 1981, Paulsen et al [15] reported the syntheses of (-)-conduritol B ( = 1~-cyclohex-5-ene-l,3/2,4-tetrol; (-)-2) and (-)-conduritol F ( = 1~-cyclohex-5-ene-l,2,4/3-tetrol; (-)-6)4).…”
Section: Synthesis Of (-)-Conduritol C (1~-cyclohex-5-ene-l23/4-tetmentioning
confidence: 99%
“…In 1958, Angyul et al [14] presented a synthesis of (+)-condurito1 E ( = 1~-cyc~ohex-5-ene-l,2/3,4-tetro~; (+)-5). In 1981, Paulsen et al [15] reported the syntheses of (-)-conduritol B ( = 1~-cyclohex-5-ene-l,3/2,4-tetrol; (-)-2) and (-)-conduritol F ( = 1~-cyclohex-5-ene-l,2,4/3-tetrol; (-)-6)4).…”
Section: Synthesis Of (-)-Conduritol C (1~-cyclohex-5-ene-l23/4-tetmentioning
confidence: 99%
“…The same approach has been applied now to the stereoselective total syntheses of (-)-conduritol B ((-)-3) which was prepared for the first time by Paulsen et al [13] and of (+)-conduritol F ((+)-1) whose characteristics were found to be identical with those of natural (+)-leucanthemitol.…”
mentioning
confidence: 89%
“…(15 ml), dried (MgSO,), and evaporated. The residue was purified by column chromatography on silica gel (Lobar, Et20/petroleum ether 1:9) yielding 2.5 g of a colourless oil containing 2.1 g (70%) of (-)- 13 [a]::6 = -17.5, [a]:& = -28.3 (c = 2.9, CHCI,). IR (film): 3260,2950(film): 3260, ,2930(film): 3260, ,2900(film): 3260, ,2860(film): 3260, ,1470(film): 3260, ,12S0,1170(film): 3260, ,1120(film): 3260, ,1080 of (-)-lZ (776 mg, 1.6 mmol) and 40% aq.…”
Section: (-)-(4 R5 S6r)-456-tris-(1 ( Tert-hutyl)dimethylsilyl]oxmentioning
confidence: 99%
“…Their ability to inhibit oligosaccharide-processing enzymes provides a wide range of possible applications in chemotherapy for these compounds, since glycoproteins are involved in numerous biochemical processes . This has stimulated enormous synthetic efforts recently, and several asymmetric approaches to these substrates have been proposed, among the most efficient of which is the microbial oxidation of aromatic precursors . We propose here a general strategy directed toward the synthesis of polyhydroxylated cyclohexanes through desymmetrization of silyl-2,5-cyclohexadienes using Sharpless asymmetric dihydroxylation .…”
mentioning
confidence: 99%
“…In summary, we have demonstrated that the desymmetrization of a readily available silyl-2,5-cyclohexadiene using asymmetric dihydroxylation affords an efficient and rapid entry into cyclohexane skeletons having four or five stereogenic centers in a stereocontrolled manner. This strategy is competitive in terms of cost, efficiency, and versatility with other approaches to similar substrates. ,, The chlorosilane precursor 4a is inexpensive, and both enantiomers are theoretically accessible. Further manipulation of intermediates such as 6 or 7 should also provide the means to access other cyclitols and related analogues.…”
mentioning
confidence: 99%